PUNISHMENT DI PONDOK PESANTREN DALAM MENJAMIN KEPASTIAN HUKUM - Salman Farisi (Universitas Nurul Jadid, 2025)
Pesantren is a religious and educational organization that develops students' independence while preserving and spreading the Islamic faith. In rural areas, pesantren also function as (traditional) social institutions. Pesantren is a non-formal educational organization established from, for, and by the community along with the spread of Islam in the archipelago. Pondok Pesantren Sabilul Hasan Genggong Probolinggo is a religious institution with a strong learning base in Islamic principles. The pesantren applies basic punishment as the main upbringing in improving themselves. The purpose of applying Qanan Asasi punishment is to form santri discipline and to enforce the rules in the pesantren environment. The character and personality of the santri are formed through this punishment so that they become religiously observant, have commendable values, and have the provisions to face obstacles in the future. Santris are taught to comply with religious standards and pesantren regulations through the use of Qanun Asasi punishment, which seeks to have a deterrent effect and teach responsibility. In addition, this punishment tries to prevent bad behavior such as rule violations, juvenile delinquency, and activities that contradict Islamic principles. This study used qualitative research methods with 3 related research subjects. The research data were collected through observation, interview and documentation techniques with data processing methods to analyze the data. Data collection is done by data reduction, data presentation and drawing conclusions from the data obtained/verification. The sanctions applied in this pesantren are in the form of Qanun Asasi provisions and direct caregiver policies, which have been adjusted to three categories of violations, namely: mild, moderate and severe.